Lonely out front? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
'After ten years of reading, for me Spore still commands the lead among agricultural magazines,' writes Martin Francis Arko, an extension agent in Ghana. He is very happy, too, with CTA's book distribution system: 'It gives us access to good study...